2018
DOI: 10.21767/amj.2018.3458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-assessment training in preclinical endodontic courses on the clinical performance of undergraduate dental students

Abstract: Background Root canal treatment (RCT) of molar teeth is very challenging to undergraduate dental students. Wellstructured self-assessment was shown to be the key for improving quality of dental education so that graduates could be properly prepared to act independently in dental practice. Aims To observe the effect of rubric self-assessment teaching during the preclinical stage on the performance of undergraduate students in treating patients' molars. Methods An improved rubric was introduced to the endodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The ability to perform self‐assessment demands practice and helps professionals understand their strengths and deficiencies 8 . Abiad showed that self‐assessment training in preclinical endodontic courses affects the clinical performance of students regarding their ability to perform root canal treatment on patients' molars before graduation with confidence 15 . Dochay et al reviewed 63 studies and concluded that self‐evaluation improved students’ performance, quality of learning and perception of problem‐solving 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to perform self‐assessment demands practice and helps professionals understand their strengths and deficiencies 8 . Abiad showed that self‐assessment training in preclinical endodontic courses affects the clinical performance of students regarding their ability to perform root canal treatment on patients' molars before graduation with confidence 15 . Dochay et al reviewed 63 studies and concluded that self‐evaluation improved students’ performance, quality of learning and perception of problem‐solving 16 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Abiad showed that self-assessment training in preclinical endodontic courses affects the clinical performance of students regarding their ability to perform root canal treatment on patients' molars before graduation with confidence. 15 Dochay et al reviewed 63 studies and concluded that self-evaluation improved students' performance, quality of learning and perception of problem-solving. 16 Abdullah et al investigated dental students' opinions on the value of self-evaluation skills and found that students' responses indicate that they consider self-evaluation as an effective educational tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations